Identification of Variable Traits among the Methicillin Resistant and Sensitive Coagulase Negative Staphylococci in Milk Samples from Mastitic Cows in India - Mahato, Sudipta; Mistry, Hiral U.; Chakraborty, Shalini; Sharma, Paresh; Saravanan, R.; Bhandari, Vasundhra (Frontiers in Microbiology, 2017)
Methicillin resistant Staphylococcus aureus causing bovine mastitis has been very well investigated worldwide. However, there are only limited reports on the characterization of methicillin resistant and sensitive coagulase negative staphylococci (CoNS) across the globe. Hence, in the present study, we aim to determine the phenotypic traits based on antimicrobial susceptibility profile and genotypic characterization by verifying the presence of resistance determinants, virulence and toxin genes present in the CoNS causing clinical mastitis. We obtained 62 CoNS isolates from 167 mastitic milk samples collected from three different states of India. The 62 isolates comprises of 10 different CoNS species S. sciuri, S. haemolyticus, S. chromogenes, S. saprophyticus, S. xylosus, S. simulans, S. agnetis, S. epidermidis, S. gallinarum and S. cohinii. Susceptibility screening against 11 antibiotics determined 45.16% isolates as multidrug resistant (resistant to more than two class of antibiotic), 46.74% resistant (one or two antibiotic class) and 8.06% isolates were pan-sensitive (sensitive to all drugs). High resistance was observed against oxacillin and cefoxitin, whereas all isolates were susceptible towards vancomycin and linezolid. 53 isolates were methicillin resistant and 9 isolates were sensitive as determined by oxacillin susceptibility assay. The methicillin resistance gene, mecA was found in 95.16% isolates and staphylococcal cassette chromosome mec (SCCmec) typing predominantly revealed Type III (n=34) and Type V (n=18). Interestingly, 11.9% of mecA positive isolates were oxacillin susceptible and referred as oxacillin susceptible mecA positive staphylococci (OS-MRS). Additionally, genes encoding for enterotoxin, (sea, seb, seh, see) toxic shock syndrome (tsst), exfoliatin (eta, etb, etd) and virulence (pvl, Y-hlg) were also screened. Of all the genes examined, 67.74% of isolate were positive for the Y-hlg gene, followed by the sea gene in 25.8% whereas in none of the isolates the eta and the etb gene was amplified. The study also highlights the incidence of clinical isolates of CoNS, which are harboring the toxin and the virulence genes rendering them as a more potential threat. This is the first report of animal origin OS-MRS from India, which emphasizes on the inclusion of both the genetic and phenotypic test for proper characterization of CoNS and preventing resistant strain misidentification.